Telehealth during the coronavirus disease 2019 pandemic: Rapid expansion of telehealth outpatient use during a pandemic is possible if the programme is previously established. (July 2022) - Schulz, Thomas; Long, Karrie; Kanhutu, Kudzai; Bayrak, Ilana; Johnson, Douglas; Fazio, Timothy
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted the health-care system both in Australia and internationally, and has rapidly transformed the delivery of health care in hospitals and the community. Implementation of social isolation and distancing measures to stop the spread of the disease and to reduce potential harm to patients has necessitated the use of alternate models of health-care delivery. Changes that would normally take months or years have occurred within days to weeks. Methods: We conducted analysis of outpatient clinic data during the period of the pandemic and compared this to previous telehealth use. We also present the results of clinician and patient telehealth experience surveys. Results: We describe a 2255% increase in the use of telehealth at a tertiary hospital within a period of six weeks, and a significant simultaneous reduction in the outpatient clinic failure-to-attend rate. The vast majority of patients and clinicians agreed that the standard of care provided by telehealth was the same as that provided by on-site appointments. Discussion: Telehealth that previously had only limited utilisation has now become a main method for the delivery of outpatient care. Clinicians and patients agreed that consultations provided by telehealth were of the same standard as those provided on site. Health care in the post-pandemic period should embed the use of telehealth for outpatient care and consider the range of other clinical contexts where this can be utilised.